(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: Menopausal health in our environment has received little attention. As a independent risk factor for dyslipidemia, the degree and pattern of derangement, though difficult to assess may adversely affect the cardiovascular health of our women. Objectives: To estimate the serum lipid profile and the atherogenic index of plasma among the pre and post- menopausal women. Materials and Methods: After an overnight fasting blood samples were collected from a group of 339 women, 140 premenopausal aged between 25-50 years and 199 postmenopausal aged between 51-70 years. Serum total cholesterol (TC), triglycerides (TG) and HDL-cholesterol were estimated by enzymatic methods and LDL-cholesterol by established mathematical methods. Atherogenic index of plasma (AIP) were calculated by using the formula (logTG/HDL-C). Statistical analysis was carried out in the two groups using the unpaired t test. Results were expressed as mean±SD. P values <0.05 were considered to be statistically significant. Results: There were statistically significant increase in serum TC (191.21±45.50 mg/dl), TG (185.83± 111.83 mg/dl) and LDL-C (118.71±38.48 mg/dl) in post-menopausal women. Their HDL-C level (38.67±10.00mg/dl) was significantly decreased. The calculated atherogenic index of plasma (AIP) was significantly higher (0.63±0.27) in post-menopausal women as compared to that in premenopausal women (0.50±0.29). Conclusion: Menopause leads to changes in lipid profile. By elevating LDL and the reduction of cardioprotective HDL is an indication that menopause is an independent risk factor for developing cardiovascular disease. These changes are caused by loss of cardio-protective effect of oestrogen. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 44-49